Analysis of source models and clustering in the characterization of corrosion-caused leaks (2019)
Use of source models and comparison with a simulation in CFD to estimate correction factors for leaks in pressurized pipes considering inclinations. The total spilled volume and the instantaneous flow in each case are used as comparison elements. Then, a clustering tool for an ILI run (In Line Inspection) is implemented in order to find the best grouping methods and the optimal number of groups to generate. These last results work to find an equivalent dimension that is introduced as a parameter in the area of a leak in the corrected source models and estimate results to make risk assessments.